2021
DOI: 10.21203/rs.3.rs-552125/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Carcass Characteristics and Egg Quality Traits of Kuroiler and Sasso Chickens Reared Under On-Station and On-Farm Management Conditions in Tanzania

Abstract: Two studies were conducted to evaluate the carcass characteristics and egg quality traits of Sasso and Kuroiler chickens under on-farm and on-station management conditions. Carcass characteristics were evaluated under on-station only while egg quality was evaluated under both management conditions. A total of 240 hens and 240 cocks were raised under on-station condition and evaluated for egg and carcass quality respectively. Meanwhile, 320 hens were raised under on-farm condition and evaluated for egg quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
2
3
1
Order By: Relevance
“…The observed genetic effect on survivability is consistent with the findings of Ajayi et al (2020). Similar observations have also been made on chickens in Nigeria (Ademola et al, 2020), Ethiopia (Kassa et al, 2021), and Tanzania (Guni et al, 2021b).…”
Section: Survivability Of Birdssupporting
confidence: 88%
See 2 more Smart Citations
“…The observed genetic effect on survivability is consistent with the findings of Ajayi et al (2020). Similar observations have also been made on chickens in Nigeria (Ademola et al, 2020), Ethiopia (Kassa et al, 2021), and Tanzania (Guni et al, 2021b).…”
Section: Survivability Of Birdssupporting
confidence: 88%
“…The present findings are consistent with the submission of Kassa et al (2021) that breed-environment interaction could influence the phenotypic expression of traits. Similar genotype by location interaction effect on growth traits has Frontiers in Genetics frontiersin.org 10 been documented in improved indigenous and tropically adapted chickens (Ajayi et al, 2020;Guni et al, 2021b). The lower mortality of birds in Nasarawa State might be attributed to better management practices, which is consistent with the findings of Alemu et al (2021).…”
Section: Figuresupporting
confidence: 75%
See 1 more Smart Citation
“…The average live body weight was 1.25 ± 0.52 kg for cocks and 1.06 ± 0.29 kg for hens. These values are lower than those reported by Moula et al (2012a) in the Kabylia region of Algeria (males -1.43 ± 0.18 kg; females -1.14 ± 0.18 kg), Getu et al (2014) in Ethiopia (males -1.63 ± 0.30 kg; females -1.37 ± 0.20 kg), Guni et al (2013) in Tanzania (males -2.10 ± 0.29 kg females -1.53 ± 0.16 kg), and Jesuyon and Salako (2013) in Nigeria (males -2.40 ± 0.14 kg; females -1.50 ± 0.14 kg). However, these results are higher than those reported by Moula et al (2012b) in the province of Bas-Congo of the DRC where the average weight of males was 1.03 ± 0.72 kg compared to 0.90 ± 0.20 kg for females.…”
Section: Discussioncontrasting
confidence: 61%
“…In the present study, the egg shape index was 73.5% (on-station) and 74% on the on-farm that is lower for on-station (75.5%) and almost similar for onfarm (73.9%) as the report of Guni et al [20] which could be explained by the size and weight of an egg. Normally egg length and width are the determinants of the shape of an egg, which were also higher for on-station eggs (57.05mm and 43mm for egg length and width, respectively) than on-farm (55.9 and 41.3mm for egg length and width, respectively)" [24]. Sokołowicz et al [25] had "a comparable observation where the egg shape index was found to be higher for birds under deep litter than those from free-range and organic systems".…”
Section: Discussionmentioning
confidence: 99%